ChemInform Abstract: Palladium‐Catalyzed Ring‐Opening of Cyclopropyl Benzamides: Synthesis of Benzo[c]azepine‐1‐ones via C(sp3)—H Functionalization. Issue 41 (19th September 2013) - Ladd, Carolyn L.; Roman, Daniela Sustac; Charette, Andre B.
Abstract A new synthesis of biologically relevant benzo[c]azepins is achieved via a novel Pd/Ag‐catalyzed intramolecular cyclization of ortho halogenated N‐cyclopropyl benzamides.